The Evolution of Nutrition Influencer Marketing: A Review (International Journal of Food and Nutritional Sciences, 2021)
This comprehensive literature review explores the dynamic landscape of nutrition influencermarketing, focusing on the evolving role of influencers in shaping consumer choices and wellnesstrends. Nutrition influencers, distinct from traditional experts, leverage social media to amasssubstantial followings, influencing food choices and lifestyle preferences. The review criticallyexamines the conceptual underpinnings of nutrition influencer marketing, highlighting the limitedacademic inquiry in this rapidly expanding field